Full Mouth Rehabilitation with All-on-Six Endosseous Implants with Upper and Lower Arch - A Case Report - Gaurav Tripathi; Juhi Thadlani; Tushar Tanwani; Gaurav Agrawal; Sudeepti Soni; Ankita Shrivastava (Journal of Pharmacy and Bioallied Sciences)
This article reports the full mouth rehabilitation of a 59-year-old male patient with completely edentulous upper and lower arches using the All-on-Six endosseous implant technique. The treatment involved placing six implants in both the upper and lower arches, followed by the placement of temporary dentures during the osseointegration period. After 15 weeks, impressions of the implants were taken using additional silicone (VPS). The final prosthesis, consisting of a Direct Metal Laser Sintering (DMLS) framework with Zirconia crowns, was designed to ensure optimal aesthetics and function. This case underscores the importance of meticulous diagnosis, planning, and treatment in the successful rehabilitation of implant-supported dentures.